2014
DOI: 10.1074/jbc.m114.600528
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Transcription and Metabolism During the Early Stage of Replicative Cellular Senescence in Budding Yeast

Abstract: Background: Senescence is the biological process of age-related cellular and organismal deterioration in function. Results: The transcriptome and metabolome at early stages of replicative senescence of yeast cells were measured. Conclusion: The transcriptomic and metabolomic profiles drastically changed at about half of the average replicative lifespan. Significance: This is the first integrated information on transcriptome and metabolome of aging yeast cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 39 publications
10
39
0
Order By: Relevance
“…Furthermore, metabolome analysis of aging yeast cells showed metabolic changes at the early stage of Abbreviations: TF, transcription factor; NMR, nuclear magnetic resonance; RTqPCR, reverse transcription-quantitative polymerase chain reaction; OPLS, orthogonal projections to latent structures. senescence, consistent with observation of human senescent cells, and such changes were caused by changing the transcript levels of the metabolic enzyme genes [14].…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…Furthermore, metabolome analysis of aging yeast cells showed metabolic changes at the early stage of Abbreviations: TF, transcription factor; NMR, nuclear magnetic resonance; RTqPCR, reverse transcription-quantitative polymerase chain reaction; OPLS, orthogonal projections to latent structures. senescence, consistent with observation of human senescent cells, and such changes were caused by changing the transcript levels of the metabolic enzyme genes [14].…”
Section: Introductionsupporting
confidence: 74%
“…Heterozygous FHL1 deletion altered the cellular metabolism and seemed to increase the content of lysine and cadaverine. Previously, we reported that lysine was accumulated in yeast senescent cells [14]. Therefore, increased content of lysine might be related to the short lifespan of Dfhl1/FHL1 mutant even though we did not find metabolic genes associated with the lifespan and catalysis of lysine and cadaverine amongst the Fhl1p-targeted genes.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…It has been suggested that the aging yeast cell, which is continuously growing in size 82, may interpret its changing cell size to volume ratio as a cue of starvation, which in turn induces these metabolic changes 1314. Supporting this, when looking at aging proteome data and the 14 proteins measured in the gene ontology for response to starvation, we see a general increase in abundances to occur with aging (Figure 2).…”
Section: Deregulated Nutrient Sensingsupporting
confidence: 61%
“…12,13 In both strains, glutamine (Gln) showed the fastest depletion, as judged by its closest proximity to the day 3 placeholder (Figure 1d and Supplementary Figure S1a). …”
Section: Resultsmentioning
confidence: 99%